Communicating about death and dying with adults with intellectual disabilities who are terminally ill or bereaved: A UK‐wide survey of intellectual disability support staff. Issue 5 (18th February 2020) - Tuffrey‐Wijne, Irene; Finlayson, Janet; Bernal, Jane; Taggart, Laurence; Lam, Claire Kar Kei; Todd, Stuart
Abstract: Background: Illness and death are part of life for everyone, including people with intellectual disabilities. This study investigated the extent to which staff communicate about death with people with intellectual disability facing terminal illness or bereavement. Method: Staff who support people with intellectual disability in the UK ( n  = 690) completed an electronic survey. Detailed data were obtained from staff where a client had died in the past 12 months ( n  = 111), was terminally ill ( n  = 41) or had been bereaved ( n  = 200). Analysis included descriptive and chi‐squared statistics. Results: 52.6% of people with intellectual disability who were terminally ill were told about their illness, and 18.1% were told they would die. Of those experiencing an anticipated bereavement, 32.4% of staff said no one talked about this with them beforehand. A quarter of staff had received training on end of life or bereavement. Conclusion: Death affects many people with intellectual disability. Staff require training and support in communicating death.